Case Study of the Merger of Military Airports in Commercial Aviation at Jenderal Ahmad Yani International Airport Semarang - Rifdlatul Aida; Irwina Meilani (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The purpose of this research is to find out what are the impacts experienced in the implementation of commercial flights at the Military Airport at General Ahmad Yani International Airport Semarang and to find out the strategy of merging Military Airports in commercial flight activities at General Ahmad Yani International Airport Semarang. This type of research is using qualitative research. Data collection instruments through observation, interviews and documentation. The results of the study stated that in the application of the rules regarding the use of military airports in commercial flights at General Ahmad Yani International Airport, Semarang, there was no significant impact on commercial flights because the operational activities of the two parties were carried out in different building locations but still using the same runway. The same.